Adoptive immunotherapy overcomes genetic susceptibility to bloodstream infections due to fc‐gamma receptor polymorphisms after liver transplantation. Issue 10 (17th June 2022) - Shimizu, Seiichi; Ohira, Masahiro; Tanaka, Yuka; Ide, Kentaro; Tahara, Hiroyuki; Kuroda, Shintaro; Tanimine, Naoki; Doskali, Marlen; Hotta, Ryuichi; Yano, Takuya; Nakano, Ryosuke; Imaoka, Yuki; et al.
Abstract: Single nucleotide polymorphisms (SNPs) in FCGR3A can predict the susceptibility of liver transplant (LT) recipients to bloodstream infections (BSI) and clinical outcomes following living‐donor LT (LDLT). Here, we retrospectively analyzed the relationship of adoptive immunotherapy with activated natural killer (NK) cells from perfusate effluents of liver allografts against BSI following LDLT. Higher BSI incidence and lower survival were observed in LT recipients with FcγRIIIa (158F/F or F/V) ( n  = 81) who did not receive adoptive immunotherapy ( n  = 55) than in those who did ( n  = 26) (BSI frequency, 36.4% vs. 11.5%; p =  .033; log‐rank p =  .047). After matching patient background using propensity score, similar results were obtained (BSI ratio, 41.7% vs. 12.5%; p =  .049; log‐rank p  = .039). The predominant BSI pathogens in patients who did and did not receive adoptive immunotherapy were gram‐negative rods ( n  = 3, 100%) and gram‐positive cocci (GPC) ( n  = 15, 65.2%), respectively. The proportion of NK cells administered to patients with BSI was significantly lower than that administered to patients without BSI (Number: 80.3 (29.9–239.2) × 10 6 cells vs. 37.1 (35.6–50.4) × 10 6 ; p  = .033, percentage; 14.1 (13.3–17.8)% vs. 34.6 (16.5–47)%, p  = .0078). Therefore, adoptive immunotherapy with NK cells was associated with the reduced post‐transplant BSI related to GPCs due to FcγRIIIa SNP in LT recipients. Abstract : Adoptive immunotherapy with activated, liver‐derived, NK cell‐enriched lymphocytes prepared from graft perfusates is associated with lower rates of post‐transplant bloodstream infection in liver transplant recipients with a genetic polymorphism of FcγRIIIa with low affinity for IgG1 and IgG3.